Factors associated with self- and informant ratings of quality of life, well-being and life satisfaction in people with mild-to-moderate dementia: results from the Improving the experience of Dementia and Enhancing Active Life programme. (9th February 2020) - Wu, Yu-Tzu; Nelis, Sharon M; Quinn, Catherine; Martyr, Anthony; Jones, Ian R; Victor, Christina R; Knapp, Martin; Henderson, Catherine; Hindle, John V; Jones, Roy W; Kopelman, Michael D; Morris, Robin G; et al.
Abstract: Background: a large number of studies have explored factors related to self- and informant ratings of quality of life in people with dementia, but many studies have had relatively small sample sizes and mainly focused on health conditions and dementia symptoms. The aim of this study is to compare self- and informant-rated quality of life, life satisfaction and well-being, and investigate the relationships of the two different rating methods with various social, psychological and health factors, using a large cohort study of community-dwelling people with dementia and carers in Great Britain. Methods: this study included 1, 283 dyads of people with mild-to-moderate dementia and their primary carers in the Improving the experience of Dementia and Enhancing Active Life study. Multivariate modelling was used to investigate associations of self- and informant-rated quality of life, life satisfaction and well-being with factors in five domains: psychological characteristics and health; social location; capitals, assets and resources; physical fitness and health; and managing everyday life with dementia. Results: people with dementia rated their quality of life, life satisfaction and well-being more highly than did the informants. Despite these differences, the two approaches had similar relationships with social, psychological and physical health factors in the five domains. Conclusion: although self- and informant ratings differ, they display similar results when focusing on factors associated with quality of life, life satisfaction and well-being. Either self- or informant ratings may offer a reasonable source of information about people with dementia in terms of understanding associated factors.